Rural social problems of repair the possibility of a primary research in the light - Demeter, Petra; Ritter, Krisztián (Studia Mundi – Economica, 2017)
This paper tries to find out how the education and elements of educational system could influence (reduce) the social inequalities as one of the main problem of rural areas. Based on the literature concerning to the integration of roma minority and disadvantaged children students of a primary school in Kiskunlacháza (Hungary) have been asked about their school motivations, preferences, free time activities, further educational plans and skills by a primary research. Comparing the results to the key findings of the literature this study recommends a mentor program as long term solution for helping the integration process of the affected students, creating a connection between the teachers and pupils based on trust, taking the needs and specialties of roma minority and disadvantaged children into account.